2022
DOI: 10.1038/s41467-022-35192-7
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor DDIT3 is a potential driver of dyserythropoiesis in myelodysplastic syndromes

Abstract: Myelodysplastic syndromes (MDS) are hematopoietic stem cell (HSC) malignancies characterized by ineffective hematopoiesis, with increased incidence in older individuals. Here we analyze the transcriptome of human HSCs purified from young and older healthy adults, as well as MDS patients, identifying transcriptional alterations following different patterns of expression. While aging-associated lesions seem to predispose HSCs to myeloid transformation, disease-specific alterations may trigger MDS development. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This work followed a retrospective, cross-sectional study design using the cBio Cancer Genomics Portal tool and the Gene Expression Omnibus (GSE) to gather clinical, mutational, and transcriptomic information on MDS patients from various datasets and studies [14][15][16][17][18][19]. The genomic data for evaluating changes in potentially useful genes came from 4,260 MDS samples from joint studies that reported cellular genomics data in 2011 held at the University of Tokyo and in Wellcome Trust Sanger Institute and others in ClinicalTrials.gov number NCT00146120, comparative study in the United States, and Wellcome Trust Sanger Institute, Hinxton, United Kingdom all in 2020 [20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work followed a retrospective, cross-sectional study design using the cBio Cancer Genomics Portal tool and the Gene Expression Omnibus (GSE) to gather clinical, mutational, and transcriptomic information on MDS patients from various datasets and studies [14][15][16][17][18][19]. The genomic data for evaluating changes in potentially useful genes came from 4,260 MDS samples from joint studies that reported cellular genomics data in 2011 held at the University of Tokyo and in Wellcome Trust Sanger Institute and others in ClinicalTrials.gov number NCT00146120, comparative study in the United States, and Wellcome Trust Sanger Institute, Hinxton, United Kingdom all in 2020 [20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…The genomic data for evaluating changes in potentially useful genes came from 4,260 MDS samples from joint studies that reported cellular genomics data in 2011 held at the University of Tokyo and in Wellcome Trust Sanger Institute and others in ClinicalTrials.gov number NCT00146120, comparative study in the United States, and Wellcome Trust Sanger Institute, Hinxton, United Kingdom all in 2020 [20][21][22][23]. The transcriptomic data found on the GSE database consists of three independent cohorts (GSE114922 in Wellcome Trust Centre for Human Genetics, United Kingdome, GSE63569 in University of Oxford, United Kingdome, and GSE183328 in CIMA, Spain) held in 2015, 2018, and 2022, respectively [14][15][16][17]. All obtained data were parallel with mutations in MDS of clinical significance.…”
Section: Methodsmentioning
confidence: 99%
“…HSPCs cells were stained using CD34-APC (clone 581; Beckman Coulter) and CD45-PerCPCy5.5 (clone HI30; Biolegend) and sorted in a BD FACSAria II (BD Biosciences). E x-vivo liquid culture differentiation assay was performed as previously described 27 . To evaluate the effect of supernatants from activated CAR-T cells, 2 mL of spCAR, spUTD or media as control were added to the differentiation process.…”
Section: Methodsmentioning
confidence: 99%
“…DDIT3 is a transcription factor induced by various adverse physiological conditions, including endoplasmic reticulum stress (Berastegui N et al 2022) ). These differences are attributed to the diverse backgrounds of tumors and diseases, the intensity and duration of stress, and the distinct cellular responses induced by DDIT3, resulting in varying outcomes.…”
Section: Ddit3 Overexpression Inhibits Bc Cell Proliferationmentioning
confidence: 99%